The physical bases of low-energy hydrogen isotope ions storage ring - Guk, I.S.; Paschenko, A.V.; Tarasenko, A.S.; Shapoval, I.N. (Вопросы атомной науки и техники, 2002)
The idea of a nonrelativistic hydrogen isotope ion storage ring is proposed. The influence of different factors on the main parameters of circulating beam is considered. The principal possibility for construction of such installation is shown.